PENDAMPINGAN PEMANFAATAN TURI (SESBANIA GRANDIFLORA) SEBAGAI PAKAN ALTERNATIF DALAM MENINGKATKAN EFISIENSI USAHA TERNAK ITIK DI DESA AIR SATAN KABUPATEN MUSI RAWAS - Syintia Dwi Agustina; Herawati Herawati; Radha Krisnamurti Sigamura; Yeni Trianah; Dhian Nurul Istiqomah; Sumini Sumini; Bagus Dimas Setiawan (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
The community service activities carried out by lecturers at Musi Rawas University in Air Satan Village were based on the high cost of feed in duck farming, which reaches around 60–70% of the total production costs. This high cost is one of the main obstacles to the development of community livestock businesses, so efforts are needed to utilize alternative feed ingredients based on local resources that are economical, easy to obtain, and have good nutritional content. One local plant that has the potential to be utilized is the white turi (Sesbania grandiflora), because it has a fairly high protein content and abundant biomass production. This activity aims to increase the insight and skills of farmers in utilizing turi leaves as an alternative feed raw material for duck farming. The implementation of the activity was carried out through extension methods, training, and demonstrations of making rations from turi leaves for farmer groups. The results of the activity showed an increase in community knowledge and ability in processing turi leaves into feed flour with a protein content of up to 29.60%. In addition, demonstration plot units were also established in farmer households as a medium for practicing and implementing simple feed processing technologies. Overall, the use of turi leaves as an alternative feed ingredient is considered capable of helping reduce production costs, increase the efficiency of livestock businesses, and support feed independence and strengthen the economy of rural communities in a sustainable manner.